A community pharmacy-based fall prevention framework across continuums of care - Abd Wahab, Mohd Shahezwan; Hazizul Hasan, Mizaton; Jamal, Janattul Ain; Mohd Rocky, Nik Ateerah Rasheeda (Faculty of Pharmacy, 2025)
Falls are a major public health concern, especially among older adults, with global and national statistics highlighting their significant impact. In Malaysia, the high prevalence of falls among the elderly population underscores the urgent need for targeted and scalable prevention strategies [1]. Falls can result in serious outcomes including injuries, loss of independence, reduced quality of life, and increased healthcare expenditure [2]. Those with a prior history of falls are at even greater risk of recurrence, necessitating early and sustained intervention.